2018
DOI: 10.1002/jmr.2739
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical recognition of taurine biomarker in unprocessed human plasma samples using silver nanoparticlebased nanocomposite: A new platform for early stage diagnosis of neurodegenerative diseases of the nervous system

Abstract: The rapid and accurate determination of the level of taurine biomarker in various tissues and body fluids can be of great interest in the early diagnosis of several important pathologies and diseases. In the present study, an innovative electrochemical interface for quantitation of taurine based on ternary signal amplification strategy was fabricated. In this work, silver nanoparticles were electrodeposited onto green and biocompatible nanocomposite containing α-cyclodextrin as conductive matrix. Therefore, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 44 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Most of the reported techniques offer several advantages, including low sensitivity, complex mobile phases, and time-consuming extraction procedures with limited applicability. A summary of the results obtained in this study compared with previously reported works is presented in Table 1, 39–45 showing that the developed method has certain advantages over previous approaches in terms of stability, suitable surface area, and feasible biological activity. Notably, our study's strengths include the utilization of a calorimetric chemosensing procedure to detect taurine in urine and blood samples for the first time.…”
Section: Resultsmentioning
confidence: 63%
“…Most of the reported techniques offer several advantages, including low sensitivity, complex mobile phases, and time-consuming extraction procedures with limited applicability. A summary of the results obtained in this study compared with previously reported works is presented in Table 1, 39–45 showing that the developed method has certain advantages over previous approaches in terms of stability, suitable surface area, and feasible biological activity. Notably, our study's strengths include the utilization of a calorimetric chemosensing procedure to detect taurine in urine and blood samples for the first time.…”
Section: Resultsmentioning
confidence: 63%
“…These properties are notably important in their biomedical applications, such as antifungal [ 66 ], anticancer [ 67 ], antiviral [ 68 ], antiangiogenic [ 69 ], antileishmanial [ 70 ] anti-inflammatory [ 71 ] and antibacterial [ 72 ] activities. Due to the global increase in life threatening diseases and the emergence of multidrug resistance in pathogens against antibiotics [ 73 ], multiple medical applications have been demonstrated for AgNPs, such as sensors for disease diagnosis [ 74 ], nanocarriers for drug delivery [ 75 , 76 ], sensitisers in radiation therapy [ 77 ], electro spin resonance dosimetry, etc. [ 78 ].…”
Section: Nanotechnologymentioning
confidence: 99%
“…Although AgNPs are well known for their antibacterial activity [ 62 ], research over the years has shown that these nanomaterials have other health-related beneficial properties. They are used in medical applications as diagnostic [ 74 ], drug delivery [ 75 , 76 ], sensitising and therapeutic agents. The global rise of the health, social and economic burden of wounds is a growing concern that necessitates novel strategies to produce sustainable solutions.…”
Section: Future Perspectivesmentioning
confidence: 99%